(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
Currently, the state faces a wide range of tasks, especially in the field of social policy implementation, some of which cannot be solved without attracting additional funds. Municipal-private partnership is one of the mechanisms for timely and high-quality resolution of local issues. This form of government-business relations is currently in the process of development, and also opens up new opportunities in the field of socio-economic development of municipalities.